2021
DOI: 10.3390/cancers13215499
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Breast Cancer Recurrence: A Systematic Review

Abstract: Breast cancer has the greatest epidemiological impact in women. Opioids represent the most prescribed analgesics, both in surgical time and in immediate postoperative period, as well as in chronic pain management as palliative care. We made a systematic review analyzing the literature’s evidence about the safety of opioids in breast cancer treatment, focusing our attention on the link between opioid administration and increased relapses. The research has been conducted using the PubMed database. Preclinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…In addition to the detrimental effects of inflammation discussed above, there remain other concerns related to chronic opioid use and tolerance in patients living with cancer. Preclinical and retrospective studies suggest a possible link between opioid use and cancer metastasis or progression 41,45 . Possible mechanisms proposed include the activation of μ opioid receptors found in malignant cells and the stimulation of cell proliferation and angiogenesis 41 .…”
Section: Inflammatory Pathways In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the detrimental effects of inflammation discussed above, there remain other concerns related to chronic opioid use and tolerance in patients living with cancer. Preclinical and retrospective studies suggest a possible link between opioid use and cancer metastasis or progression 41,45 . Possible mechanisms proposed include the activation of μ opioid receptors found in malignant cells and the stimulation of cell proliferation and angiogenesis 41 .…”
Section: Inflammatory Pathways In Cancermentioning
confidence: 99%
“…Some opioids have been shown to inhibit the activity and cytotoxicity of immune cells 41 . Notably, although several retrospective studies have shown that opioid use is associated with decreased survival in several cancer types, 46–49 this link has not been confirmed through prospective clinical trials, and opioids remain a primary component of cancer pain management 45,41,50,51 . Still, the inflammatory nature of pain and opioid use requires further investigation into their potential role in depression and poor outcomes.…”
Section: Inflammatory Pathways In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported a protective association between intraoperative opioid use and recurrence-free survival in triple negative breast cancer [ 10 ]. Conclusions of systematic reviews evaluating the effects of opioids in patients with cancer have a common theme: there is a lack of robust evidence and high-quality trials in humans [ 11 , 12 , 13 •]. Evaluation of the association between intraoperative opioid use and clinically relevant cancer outcomes is crucial to gain insight into how the cellular effects may affect longer-term outcomes, such as survival endpoints.…”
Section: Introductionmentioning
confidence: 99%